The Use of Trajectory Cluster Analysis to Evaluate the Long-Range Transport of Black Carbon Aerosol in the South-Eastern Baltic Region - Steigvilė Byčenkienė; Vadimas Dudoitis; Vidmantas Ulevicius (Advances in Meteorology)
Trajectory cluster analysis and source-receptor models (the potential source contribution function (PSCF), concentration weighted trajectories (CWT), and trajectory source apportionment (TSA)) were applied to investigate the source-receptor relationship for the aerosol black carbon (BC) measured at the coastal site (Preila, 55.55°N, 21.04°E) during 2013. The main sources and paths of advection to the south-eastern Baltic region and its relation to black carbon concentration were identified. The 72 h backward trajectories of air masses arriving at Preila from January to December 2013 were determined and were categorized by clustering them into six clusters. Subsequently, BC levels at Preila associated with each air mass cluster during this period were analyzed. The PSCF and CWT analysis shows that, on high BC concentration days, the air masses commonly originated and passed over southern regions of Europe before arriving at Preila in winter, while a strong impact of wildfires was observed in spring.